PENGEMBANGAN MULTIMEDIA PEMBELAJARAN TEORI KINETIK GAS BERBANTUAN CAMTASIA STUDIO - Syukra, Ilman Masrul; Aunurrahman, Aunurrahman; Mering, Aunurrahman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
ABSTRACTThis development research's aim to produce multimedia learning of gas kinetic theory with assisted camtasia studio as an effort to improve student learning's outcomes and to overcome  limitations of media learning that suitable with the learning characteristics of class XI MIA's student at SMAN 2 Tebas, Sambas Regency. The research method refers to the Borg and Gall step but due to the time constraint, the steps which are carried out were only six, namely: preliminary research; planning; initial product development; limited trial; major product revision; and field trial. The product development design that is used in this research is the ASSURE model, which is: to analyze the student characteristics; set the learning goals; to select the methods, media and teaching materials; to utilize the media and the teaching materials; to involve the student participation; and to evaluate and to revise the products. The multimedia products are declared 'worthy to be used / to be tested' after being validated by expert validators namely design and learning strategy expert, instructional media expert, and learning content expert with an average rating of 4.28 and the criteria for product quality is  'very good'. The use of the product has a positive impact to increase the student learning outcomes' average (? KKM), from 53% at pretest to 90.63% at posttest or an increase of 37.50%. From the calculation's result obtained the effectiveness of product usage (effect size) to 1.6 the student learning's outcome (high effect) with 94.5 percentage. Keywords: Development, Multimedia Learning, Gas Kinetic Theory